ANALISIS FUKUGOUDOUSHI DASU DALAM ANIME KIMETSU NO YAIBA KARYA KOYOHARU GOTOUGE - Fikry Ramadhan; Damai Yani (Universitas Negeri Padang, 2022)
This study discusses the meaning of fukugoudoushi dasu contained in the anime kimetsu no yaiba by Koyoharu Gotouge. This reseach is a qualitative type with descriptive method. The data in this study are in the from of words or sentences containing fukugoudoushi dasu in the anime kimetsu no yaiba. The data source in this study is the anime kimetsu no yaiba by koyoharu gotouge. Instrument of this research is the researcher herself. In this research, researcher found 22 data fukugoudoushi dasu, divided into 4 meanings, they are : 4 meanings of displacement, 13 meanings of manifestation, 2 meanings of creating something, and 3 meanings of discovery. The conclusion of this research is that in general the data found are types of words from fukugoudoushi which are formed following the prepositions of the word.